2020
DOI: 10.1007/s12262-020-02592-2
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Real-Time Online Teaching During COVID Era Among Surgery Postgraduates

Abstract: A cross-sectional study was conducted to assess the utility of online teaching for general surgery postgraduate residents at the end of 1 month of online teaching during the COVID-19 lockdown. A questionnaire related to different aspects of online teaching was developed on a 5-point Likert scale from “strongly agree” to “strongly disagree”. Following a pilot study, the questionnaire was shared among surgery residents, and response collection was done. The residents who did not attend at least 90% of scheduled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
(23 reference statements)
3
9
0
1
Order By: Relevance
“…Trainees' perception and acceptance have been a satisfactory and positive response towards the blended learning system. It was received favourably by 54.6 % in our study, similar to previous studies conducted on blended learning in the past [ 16 - 20 ]. In a study published in the American Journal of Surgery, the response of most surgical residents was positive in regards that the approach of blended learning was providing a curriculum that educates them virtually but face-to-face in person.…”
Section: Discussionsupporting
confidence: 91%
“…Trainees' perception and acceptance have been a satisfactory and positive response towards the blended learning system. It was received favourably by 54.6 % in our study, similar to previous studies conducted on blended learning in the past [ 16 - 20 ]. In a study published in the American Journal of Surgery, the response of most surgical residents was positive in regards that the approach of blended learning was providing a curriculum that educates them virtually but face-to-face in person.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the fact that students could communicate in real time using videoconferencing tools, forums, chats, they lack face-to-face communication, which correlates with the first survey question, where only 10% students agree that Pediatric Surgery can be studied fully online. This result is in line with Srivastava et al [42] where it was found that the students' evaluation of online surgical classes was borderline when compared with physical class, although the communication with the teacher was well coordinated.…”
Section: Resultssupporting
confidence: 90%
“…Teaching online is different from classroom teaching, especially since postgraduate medical teaching is largely a problem based rather than the didactic. [ 20 ] Multiple studies have shown that accessibility, flexibility, and increased interactivity with co-participants and communication in a coordinated manner are key to student satisfaction when it comes to online learning. Students have also reported that lack of interaction with the teacher and lesser in-depth group discussion for clarification as drawbacks of e-teaching program.…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended that the online webinar-based model is used to supplement, but not replace, clinical training and face-to-face learning opportunities. [ 18 20 22 ] Given that the resumption of classroom teaching is not set to resume in the foreseeable future, the power of webinars should be harnessed appropriately and judiciously, without inducing "webinar fatigue." Our survey shows that, as of now, ophthalmology trainees in India found online teaching programs and webinars to be useful in enhancing their theoretical knowledge and practical skills/surgical learning.…”
Section: Discussionmentioning
confidence: 99%